Anticipatory Anxiety and Wishful Thinking - Engelmann, Jan B.; Lebreton, Maël; Salem-Garcia, Nahuel A.; Schwardmann, Peter; van der Weele, Joël J. (American Economic Review, 2024)
Across five experiments (N = 1,714), we test whether people engage in wishful thinking to alleviate anxiety about adverse future outcomes. Participants perform pattern recognition tasks in which some patterns may result in an electric shock or a monetary loss. Diagnostic of wishful thinking, participants are less likely to correctly identify patterns that are associated with a shock or loss. Wishful thinking is more pronounced under more ambiguous signals and only reduced by higher accuracy incentives when participants’ cognitive effort reduces ambiguity. Wishful thinking disappears in the domain of monetary gains, indicating that negative emotions are important drivers of the phenomenon. (JEL C91, D12, D83, D91)